2023
DOI: 10.1021/acsanm.2c03803
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Semiconducting 2D Nanofilms of Janus WSi2P2As2 for Applications in Sub-5 nm Field-Effect Transistors

Abstract: Searching for eligible two-dimensional (2D) semiconductors to fabricate high-performance (HP) short-channel field-effect transistors (FETs) at the nanoscale is essential toward the continuous miniaturization of devices. Herein, we predict the 2D Janus WSi2P2As2 semiconductor and propose it as a qualified channel material for sub-5 nm FETs by using first-principles calculations. The results demonstrate that the monolayer Janus WSi2P2As2 is a 2D semiconducting nanofilm with a band gap of 0.83 eV, a hole mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…To assess the potential of the ML-NbS 2 FET with the high-κ dielectric for HP applications at supply voltages of 0.64 V, we compare the I on , PDP, and τ of several HP 2D FETs based on MoS 2 , MoSi 2 N 4 , WSi 2 P 4 As 4 , GaO 3 , and selenene, using the ITRS standards as a benchmark in Figure a,b. The I on of the ML-NbS 2 FET meets the ITRS standards and is significantly higher than those of other FETs.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the potential of the ML-NbS 2 FET with the high-κ dielectric for HP applications at supply voltages of 0.64 V, we compare the I on , PDP, and τ of several HP 2D FETs based on MoS 2 , MoSi 2 N 4 , WSi 2 P 4 As 4 , GaO 3 , and selenene, using the ITRS standards as a benchmark in Figure a,b. The I on of the ML-NbS 2 FET meets the ITRS standards and is significantly higher than those of other FETs.…”
Section: Resultsmentioning
confidence: 99%
“…20 Two-dimensional Janus materials greatly enhance the function of FETs due to the intrinsic built-in electric field resulting from symmetry breaking. 21–23 Furthermore, the low power delay, 24 low on-state current 25 and ultrasmall gate length 26 of FETs are realized with the applications of 2D Janus materials, which demonstrate that Janus B 2 P 6 has great potential to be a channel material.…”
Section: Introductionmentioning
confidence: 99%
“…Recent demonstrations have showcased their prowess in diverse technologies, including transistors, spintronics, thermoelectrics and magnetic devices, firmly establishing Janus 2D materials as promising candidates for high-performance solid-state devices. [18][19][20][21][22][23][24][25][26][27] Xu et al discovered novel MXY (M = Sb, As; X = Te, Se; Y = Br, I) monolayers with semiconducting behavior, strong optical absorption in the visible to near-ultraviolet region, notable piezoelectricity, and large dielectric constants, showing promise for piezotronics, piezo-phototronics, and high-performance optoelectronic solar energy devices. 28 Additionally, Wang et al demonstrated that Janus AsXY (X = Se, Te; Y = Br, I) monolayers exhibit stability, semiconducting behavior, strong optical absorption, and high carrier mobility in the visible region, making them promising candidates for electronics, optoelectronics, and photocatalytic water splitting applications under external potential in an acidic environment.…”
Section: Introductionmentioning
confidence: 99%